Diallel analysis in chilli for horticultural characteristics and resistance to pepper veinal mottle virus - Soh, A. C.; Yap, Thoo Chai; Graham, K. M. (1977)
Pepper veinal mottle virus (PVMV) belonging to the potato virus Y group, has a wide distribution (Brunt and Kenten, 1972; Lana et al. 1975; Ong, 1975) and causes a serious disease of chilli ~(Cllpsicumannuum L.). Some chilli collections from Chiangmai, Thailand were observed in preliminary trials to be Held resistant (mild mottling). An F1 diallel cross experiment involving resistant, moderately susceptible, and susceptible lines was designed to study the inheritance of PVMV resistance and to determine genetic variance and heritability estimates for certain horticultural characteristics.